Financial Technology Strategies in Overcoming Financial Inequality and Improving Financial Access - Mohamad Kohirudin; Thomas Soseco; Vika Annisa Qurrata; Etty Soesilowati (International Journal Business, Management and Innovation Review, 2025)
This study analyzes the role of financial technology (fintech) strategies in addressing financial inequality and improving access to financial services in Indonesia. Fintech, through innovations like e-wallets, technology-driven lending, and micro-investments, plays a crucial role in promoting financial inclusion, especially for communities underserved by traditional banking systems. By leveraging digital platforms, fintech can offer affordable and accessible financial services to a broader segment of the population, particularly in rural or remote areas where conventional financial institutions have limited reach. The research employs a qualitative approach using a literature review of reports and publications from reputable sources, such as Bank Indonesia, the Financial Services Authority (OJK), and global fintech industry analyses from the past decade. The findings emphasize three key pillars for effectively reducing financial gaps: fostering collaboration between traditional financial institutions and fintech companies, enhancing financial and digital literacy, and strengthening regulatory frameworks and digital infrastructure. Through these strategies, fintech has the potential to drive economic growth, reduce poverty, and promote social welfare. The study concludes that fintech can be a catalyst for creating an inclusive, equitable, and sustainable financial system, thus contributing to Indonesia’s overall development and social well-being. These strategies align with broader efforts to build a more resilient and inclusive economy.